Macroinvertebrados aquáticos em riachos de cerrado: abordagens ecológicas teórica e aplicada - Saito, Victor Satoru (2013)
The aquatic macroinvertebrates are widely used in ecological studies and recently applied for biomonitoring. The knowledge about composition and distribution patterns are essential to elaborate environmental biomonitoring programs. The Cerrado vegetation, considered hotspot of biodiversity, is one of the most threatened savanna in the world and due to this importance its biodiversity and natural resources needs their own methodology for monitoring. In view of the above this thesis was divided in two studies: 1) Study about the variation in faunal composition of the metacommunity and the importance of local variables and spatial variables. 2) Development of a regional multimetric index using metrics from the macroinvertebrates community. Both studies used the database of 21 streams from the central region of São Paulo State, being 14 impacted streams (seven of sugarcane monocultures and seven of pasture) and seven reference streams, inserted in conserved Cerrado areas. The results of the first paper showed a metacommunity influenced by local factors and little variation was explained by spatial factors. These results fits the studied metacommunity in the species sorting model, considered the ideal for bioindicator groups. In the second paper the filters tested the metrics for range, sensibility to anthropic impact, redundancy between metrics, correlation to natural variability of streams and simplicity. The following metrics passed all filters: of EPT richness to family level, Shannon s Diversity Index to family, percentage of Trichoptera, EPT/Chironomidae and Biological Monitoring Working Party adapted index. The 5 developed multimetric index use metrics of low taxonomic resolution and good response to environmental impact, showing a potential for application in biomonitoring programs in the studied region.